EFFECT OF ACUPUNCTURE AND EXERCISE THERAPY ON MUSCULAR STRENGTH, LYMPHEDEMA, AND QUALITY OF LIFE IN BREAST CANCER SURVIVORS - Giron, Patricia Santolia; Haddad, Cinira Assad Simão; Rizzi, Samantha Karla Lopes de Almeida; Elias, Simone; Nazário, Afonso Celso Pinto; Facina, Gil (Mastology, 2026)
Objective: The aim of this study was to compare three distinct rehabilitation treatments (exercise therapy, acupuncture, and Stiper®) in women undergoing breast cancer surgery, assessing strength, lymphedema, and quality of life. Methods: In all, 79 women with pain above 3 on the visual analog pain scale (VAS) and with more than 90 days of surgery were included. They were divided into three groups that received weekly treatment for 10 weeks: group I (G1) treated with standard, predefined exercise therapy, based on stretching of the cervical muscles, shoulder girdle, and shoulder ROM exercises with a duration of 30 min; group II (G2) treated with 30 min of acupuncture using predefined points; and group III (G3) treated with the same acupuncture points as group II, however, using the Stiper® (silicon oxide micronized quartz pellet) in place of needles. Results: A total of 67 patients completed the treatment – 26 from G1, 23 from G2, and 18 from G3. There was an improvement in upper limb muscle strength over time in all groups, except for abduction and internal rotation movements. During treatment, there was no increase in the number of patients with lymphedema, and there was no statistical difference between the groups. Regarding the EORTC QLQ-C30 quality of life questionnaire, 9 of the 15 factors analyzed showed significant differences between sessions. The factors that did not have significant differences between the three groups were social function, nausea and vomiting, dyspnea, loss of appetite, constipation, and diarrhea. Conclusion: The rehabilitation of physical dysfunctions in women who survived breast cancer through exercise therapy, acupuncture, and Stiper® in upper limb muscle strength, lymphedema, and quality of life proved to be effective without superiority between groups, which leads to the conclusion that acupuncture showed equivalence of results when compared with exercise therapy, thus being an effective approach for the rehabilitation of these women.